2013
DOI: 10.1088/0004-637x/769/2/96
|View full text |Cite
|
Sign up to set email alerts
|

FLARE-ASSOCIATED TYPE III RADIO BURSTS AND DYNAMICS OF THE EUV JET FROM SDO/AIA ANDRHESSIOBSERVATIONS

Abstract: 26We present a detailed description of the interrelation between the Type III radio 27 bursts and energetic phenomena associated with the flare activities in Active region 28 AR 11158 at 07:58 UT on 2011, Feb. 15. The timing of the Type-III radio burst 29 measured by the radio wave experiment on the Wind/WAVE and an array of 30 ground-based radio telescopes, coincided with an EUV jet and hard X-ray emission 31 observed by SDO/AIA and RHESSI., respectively. There is clear evidence that the 32 EUV jet shares the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 27 publications
2
28
1
Order By: Relevance
“…in the photosphere (Hα, Ca II K surges), chromosphere (UV), transition region (EUV) and corona (X-ray). Jets can occur in different environments such as coronal holes (CHs; Young & Muglach 2014a,b), and active regions (ARs; Innes et al 2011;Chen et al 2013;Schmieder et al 2013;Chandra et al 2015), where they have different manifestations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…in the photosphere (Hα, Ca II K surges), chromosphere (UV), transition region (EUV) and corona (X-ray). Jets can occur in different environments such as coronal holes (CHs; Young & Muglach 2014a,b), and active regions (ARs; Innes et al 2011;Chen et al 2013;Schmieder et al 2013;Chandra et al 2015), where they have different manifestations.…”
Section: Introductionmentioning
confidence: 99%
“…The statistical study of X-ray jets (Shimojo et al 1996) observed by Soft X-ray Telescope (SXT; Tsuneta et al 1991) onboard Yohkoh (Ogawara et al 1991) Movies are available in electronic form at http://www.aanda.org showed that jets most often occur in the western periphery of the leading spot. Other high-resolution observations showed that jets that occur at the periphery of the active regions/sunspots are mostly associated with a nonthermal type-III radio burst which is known to be produced by energetic electrons that gyrate along the open magnetic field lines (Kundu et al 1995;Raulin et al 1996;Innes et al 2011;Chen et al 2013;Chandra et al 2015). Also, it has been observed that the accelerated electrons which have access to open field lines produce impulsive, electron/ 3 He-rich solar energetic particle (SEP) events in the interplanetary medium (Nitta et al 2008;Wang et al 2006) and the accelerated electrons which are trapped in closed field lines travel downwards, lose their energies owing to collision, and produce hard X-ray emission (HXR; Glesener et al 2012;Chen et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculated temperature may represent the average temperature of the plasmas along the LOS. The other method is differential emission measure (DEM) based on the multi-thermal nature of the plasmas along the LOS (Doschek et al 2010;Chandrashekhar 2014b;Kayshap et al 2013;Chen et al 2013;Sun et al 2014b), which is more realistic and reasonable. Occasionally, hard X-ray (HXR) sources could be detected at the bottom of jets, and the hot thermal component could be isolated during the fittings to perform temperature diagnostic (Bain & Fletcher 2009;Krucker et al 2011;Glesener et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Many papers report a significant delay between jet formation and flux emergence in contrast to recent 3D Early observations of X-ray jets associated with bursts of metric radio emission implied that the jet mechanism was able to accelerate sub-relativistic electrons along dense corona structures (Aurass et al 1994;Kundu et al 1995;Raulin et al 1996). Further confirmation came from observations of jets which were co-incident with hard X-rays from their footpoints (Chen et al 2013;Krucker et al 2011;Nitta 1997;Nitta et al 2008) and from the jet itself (Bain & Fletcher 2009;Glesener et al 2012).…”
Section: Introductionmentioning
confidence: 98%